Quality of information given to surgical patients with abdominal cancer - Guimarães Ferreira da Silva, Daniela; Pessoa de Souza, Ana Lucia Lira; Cassia de Freitas Martins, Thalyta; Martins Pedrosa, Thais; Drumond Muzi, Camila; Mendonça Guimarães, Raphael (Investigación y Educación en Enfermería, 2017)
Objective. To evaluate the need for information in patients with abdominal neoplasms. Methods. The sample consisted of 100 patients hospitalized in a surgical ward for patients with abdominal neoplasms at the National Institute of Cancer José de Alencar Gomes da Silva / INCA, in the period between June and December 2016. To collect the data, the Brazilian Portuguese version of the European Organization for Research and Treatment of Cancer (EORTC) information module questionnaire (QLQ-INFO25) was used. Results. In general, for most items, the patients showed satisfaction with the amount of information received. The items referring to the disease, examinations, treatment and general information stand out, with an average score of more than 80%. For some items, however, there is dissatisfaction with the amount of information received, especially those related to the cause of the disease, aspects of out-of-hospital and home care, different places of care and aspects of self-help, with a satisfaction level of less than 40%. Conclusion. Despite the high level of satisfaction with the information received, it was observed that almost all patients would like more information, which makes us recommend that, as part of the care, the information offered to these patients about the treatment and the evolutionary process of the disease should be enhanced. How to cite this article: Silva DGF, de Souza ALLP, Martins TSF, Pedrosa TM, Muzi CD, Guimarães RM. Quality of information given to surgical patients with abdominal cancer. Invest. Educ. Enferm. 2017; 35(2):221-231.